Influence of Melatonin as an Antioxidant on the Preservation of Liquid Ram Semen in Tris-Fructose Egg Yolk Diluent - Pattikawa, Vapriel Andhika; Karja, Ni Wayan Kurniani; Fahrudin, Mokhamad; Prasetyaningtyas, Wahono Esthi (IPB University, 2025)
Excessive free radicals can induce oxidative stress, leading to the inhibition of phosphorylation processes that supply energy for sperm capacitation and the acrosome reaction in spermatozoa during fertilization. This study investigated the impact of incorporating the antioxidant melatonin into the tris-fructose egg yolk diluent on the quality of ram liquid semen preserved at 4°C. Fresh semen with ≥70% motility was diluted in the tris-fructose egg yolk group (control), tris-fructose egg yolk with 0.5 mM melatonin (TFEY + M0.5), tris-fructose egg yolk with 1 mM melatonin (TFEY + M1), tris-fructose egg yolk with 2 mM melatonin (TFEY + M2). Semen was stored in the refrigerator at 4°C for 5 days (D0−D5). The motility, viability, abnormality, and plasma membrane integrity of the semen were evaluated every 24 hours. The results indicated no significant difference (P>0.05) between the control group and the liquid semen treatment at D0. Liquid semen quality was significantly improved with melatonin treatment compared to the control group. The results of this study indicate that TKTF + M0.5 had the highest motility and viability values ​​and can maintain abnormality values. The TKTF + M2 group had a higher plasma membrane integrity value than the other treatment groups.